(untitled) (Annals of Medical Research, 2021)
Aim: Kidney transplantation is the most effective treatment for end stage renal disease in all age groups. In this study, we analyzed our surgical complications after pediatric kidney transplantation. Materials and Methods: The data of pediatric patients who underwent kidney transplantation in our center between April 2009 and April 2019 were retrospectively analyzed. We divided the complications of the patients requiring secondary surgery into two groups as early and late according to their appearance in the first week and after. Wound problems, local or systemic infections, incisional hernias were not included in the surgical complication group. Results: Among the 27 pediatric kidney transplant procedures performed in our center, there were 11 surgical complications (6% early and 5 late complications) (40%). 4 of the complications in the early transplant period were due to bleeding, 1 was due to the torsion of the vascular structures belonging to the graft, and 1 was due to lymphocele development. Three of the late complications were ureteral stenosis, and two were due to vesicoreteral reflux to the transplant kidney. In our study group, there was no patient loss due to transplantation. Graft loss was not related to surgical complication in any patient. Conclusion: Pediatric kidney transplantation is a procedure that can be safely performed in our center, by looking at our patient and graft survival results and low surgical complications. Immediate identification and treatment of any complications are critical to the graft and patient survival.